Effectiveness of Melongas Toddler Massage on Appetite and Sleep Quality of Stunting Toddlers - Widani Darma Isasih; Junendri Ardian; M. Thonthowi Jauhari (AgriHealth: Journal of Agri-food, Nutrition and Public Health, 2025)
Stunting is a condition of growth failure in toddlers, with the incidence rate in the North Lombok Regency reaching 19.3% in 2023. Although melongas, a traditional message technique widely practiced by the local community, is believed to support growth and development, there is currently no scientific evidence validating it in addressing stunting. The research aims to determine melongas massage’s effectiveness on stunted toddlers’ appetite and sleep quality. The research method uses a quantitative approach, a quasi-experimental with a nonequivalent control group design. The sampling technique uses saturated sampling. The research population consisted of 96 toddlers. Massage for toddlers using melongas method is carried out 2 times a week, lasting 10 to 15 minutes for 4 weeks. Data were analyzed using the Wilcoxon signed-rank test. The result revealed that most stunted toddlers who received massage therapy based on the melongas method experienced a significant improvement in appetite (47.91%) and sleep quality (75%). This study examines the relationship between massage therapy based on the melongas method and stunted toddlers’ appetite ( -value 0.021) and sleep quality ( -value 0.025). Toddler massage using the melongas method effectively increases stunted toddlers’ appetite and sleep quality.